Effect of skin and coat characteristics on growth and milk production traits in Tharparkar cattle - RASHID, SOFI AAQIB; TOMAR, ATUL KUMAR SINGH; VERMA, MED RAM; MEHROTRA, SANJEEV; BHARTI, PANCH KISHOR (The Indian Journal of Animal Sciences, 2019)
The present study was conducted on a total of 68 Tharparkar cattle (Bos indicus) at Cattle and Buffalo farm (Indian Veterinary Research Institute) from December 2016 to April 2017. The objective was to study the effect of skin and coat characteristics like coat colour, coat score (CS) coat thickness, hair density, hair length, hair diameter and weight of hair coat on growth (live body weights at birth, 3, 6, 12, 18 and 24 months of age) and milk production (Lactation lengths, lactation milk yield) traits. Physiological parameters studied were skin temperature (ST), rectal temperature (RT) and respiration rate (RR). Animals were divided into 2 groups: light grey (LG) and dark grey (DG), on the basis of coat colour. Higher average body weights were found in light grey animals at 3, 6, 12, 18 and 24 months of age. An increase in coat score (higher coat score implies rough, long and a more wooly hair coat) tended to have a negative effect on body weight gain as well as on milk production. The average previous lactation yields of LG were higher than DG group. Cattle with lower hair densities (<400 hair/cm2) had higher milk yields than with higher hair densities (>400 hair/cm2). Considering the results of the present study, it can be concluded that skin and coat characteristics can be used as a potential selection tool to improve growth and production potential of cattle especially in tropics.